(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This thesis examines how Uzbekistan can strengthen its national innovation system and drive economic development through targeted reforms in science policy and public sector management. It analyzes innovation challenges and opportunities based on a literature review, statistical analysis, case studies, and stakeholder interviews. Reform recommendations are proposed to optimize university-industry linkages, encourage private R&D investment, streamline bureaucracy faced by startups, and improve the skills of civil servants through performance-based training. The goal is to provide evidence-based policy strategies for Uzbekistan to enhance its innovation capacity and transition to an innovation-driven economy.